Peliosis hepatis induced by 6-thioguanine administration. Issue 9 (September 1988) - Larrey, D; Fréneaux, E; Berson, A; Babany, G; Degott, C; Valla, D; Pessayre, D; Benhamou, J P
Abstract : A patient with acute myeloblastic leukaemia developed jaundice revealing peliosis hepatis after receiving 6-thioguanine for two months. Peliosis hepatis was severe and was associated with mild lesions of centrilobular veins. Withdrawal of 6-thioguanine was followed by a progressive improvement of liver dysfunction. This report shows that 6-thioguanine, a thiopurine already reported to be responsible for veno-occlusive disease of the liver, can induce peliosis hepatis. This suggests that some liver vascular disorders caused by thiopurines (6-thioguanine, azathioprine and 6-mercaptopurine), particularly peliosis hepatis, veno-occlusive disease, sinusoidal dilatation and perisinusoidal fibrosis, might be related syndromes caused by similar lesions at different sites.